Personagens e escrita diante do espelho: a questão do duplo em quatro romances de Roberto Drummond - BORGES, Ronaldo Elias (2009)
This study aims at analyzing the theme of the double in four novels written by Roberto Drummond: Ontem à noite era sexta-feira (1988), Hilda Furacão (1991), Inês é morta (1993) and O Cheiro de Deus (2001). Based on the examination of the procedures used by the author to constitute the double in the works previously mentioned, we verified that this element was mostly used by characters who were either their own double or twin brothers. When it comes to the first case, we can observe it in Inês é morta; the second one, in Ontem à noite era sexta-feira as well as in O cheiro de Deus. In addition to this, it is relevant to point out that in our study, we found out that Roberto Drummond duplicated both his characters as his own writing, constituting what we call, in this study, as the double of the writing. We analyzed such narrative strategy in the following novels: Hilda Furacão, Ontem à noite era sexta-feira and O cheiro de Deus. For the development of this study, we learned on the studies carried out by the following authors: Nicole Bravo, Yves Pélicier and Ana Maria Lisboa de Mello as far as the myth of the double is concerned and in the considerations made by Sigmund Freud, Otto Rank and Clément Rosset in relation to the splitting of the Self, as well as in Lucien Dällenbach s and Linda Hutcheon s reflections about the narrative procedures concerning mise en abyme and metafiction respectively.